Polymorphism of the manganese superoxide dismutase gene but not of vascular endothelial growth factor gene is a risk factor for diabetic retinopathy - Tiia Kangas‐Kontio; Satu Vavuli; Sakari Kakko; James Penna; E-R Savolainen; Markku J. Savolainen; Johanna Liinamaa (2009)
Background: In diabetic retinopathy, the vascular endothelium is damaged due to oxidative stress and inflammation, and vitreous VEGF concentration becomes elevated. The association of diabetic retinopathy with single nucleotide polymorphisms (SNPs) was studied on two genes: VEGF, an important mediator of neovascularisation, and MnSOD, a major antioxidant enzyme. Methods: The study population was 755 individuals consisting of 131 diabetic (type 1 or type 2) patients with diabetic retinopathy (DR group), 98 diabetic controls without retinopathy (DC group) and 526 non-diabetic controls. VEGF SNPs rs699947, rs2010963, rs2146232, rs3025033, rs3025039 and Ala16Val polymorphism of the MnSOD gene were genotyped. Results: The frequencies of allele and genotype of the single genotyped VEGF SNPs or reconstructed haplotypes of these single SNPs did not differ between DR and DC groups. A higher frequency of the AlaAla genotype (p = 0.03) and Ala16 allele (p = 0.04) of the MnSOD gene in the DR group was found when compared with the DC group. Conclusions: In conclusion, the studied VEGF SNPs were not associated with the risk of diabetic retinopathy, and so it is unlikely that the VEGF gene is a major locus determining the risk of diabetic retinopathy. A statistically significant association of MnSOD Ala16Val polymorphism with diabetic retinopathy was found.